Antibiogram of Escherichia coli isolates obtained from cases of neonatal calf diarrhoea in Kerala - Saritha Baby; Chintu Ravishankar; Koshy John; M. Mini; S. Ajithkumar; P. Vinu David (Journal of Veterinary and Animal Sciences, 2023)
A study was conducted to determine the antibiogram of Escherichia coli isolated from cases of neonatal calf diarrhoea in Thrissur and Wayanad districts of Kerala. A total of 101 isolates were tested for susceptibility against 12 antibiotics. The antibiotics to which the isolates were most susceptible were Streptomycin (49.51%) and Chloramphenicol (47%). The isolates showed varying degrees of susceptibility to the other antibiotics tested such as Enrofloxacin (8.92%), Ciprofloxacin (15.85%), Gentamicin (23.77%), Tetracycline (20.8%), Amoxicillin/sulbactam (8.92%), Co-trimoxazole (20.8%), and Nitrofuratonin (25.75%). All the isolates were resistant to Cefpodoxime, Penicillin G and Cefotaxime/Clavulanic acid. Many of the isolates were found to be multi-drug resistant which has serious implications for the control of these infections through antibiotic therapy.